2018
DOI: 10.1074/jbc.ra118.003897
|View full text |Cite
|
Sign up to set email alerts
|

d-2-Hydroxyglutarate dehydrogenase plays a dual role in l-serine biosynthesis and d-malate utilization in the bacterium Pseudomonas stutzeri

Abstract: is a very large bacterial genus in which several species can use d-malate for growth. However, the enzymes that can metabolize d-malate, such as d-malate dehydrogenase, appear to be absent in most species. d-3-Phosphoglycerate dehydrogenase (SerA) can catalyze the production of d-2-hydroxyglutarate (d-2-HG) from 2-ketoglutarate to support d-3-phosphoglycerate dehydrogenation, which is the initial reaction in bacterial l-serine biosynthesis. In this study, we show that SerA of the strain A1501 reduces oxaloacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Although D-2-HGDH exhibits also a slightly weaker binding ( K m ) with D-LAC (1.3-fold), it has a significantly low k cat for D-LAC (13.5-fold) (Supplementary Table S1 ). Similar results were also observed for P. stutzeri D-2-HGDH 39 . Consistently, SPR analyses show that D-2-HGDH has a tighter binding with D-2-HG ( K d of 149 μM) than D-MAL ( K d of 799 μM) and D-LAC ( K d of 1.62 mM) (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Although D-2-HGDH exhibits also a slightly weaker binding ( K m ) with D-LAC (1.3-fold), it has a significantly low k cat for D-LAC (13.5-fold) (Supplementary Table S1 ). Similar results were also observed for P. stutzeri D-2-HGDH 39 . Consistently, SPR analyses show that D-2-HGDH has a tighter binding with D-2-HG ( K d of 149 μM) than D-MAL ( K d of 799 μM) and D-LAC ( K d of 1.62 mM) (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Previous biochemical data showed that D-2-HGDH exhibits high activity towards D-2-HG, moderate activity towards D-LAC and D-MAL, but no activity towards L-2-HG 17,38,39 . Our biochemical data show that D-2-HGDH exhibits high specific activities towards both D-2-HG (2.02 ± 0.04 μmol/min/mg) and D-MAL (2.52 ± 0.05 μmol/ min/mg), a very weak activity towards D-LAC (0.16 ± 0.01 μmol/min/mg), and a negligible activity towards L-2-HG (0.06 ± 0.01 μmol/min/mg) ( Fig.…”
Section: Substrate Specificity and Stereo Selectivitymentioning
confidence: 95%
“…To this end, the glutarate pathway described here has to be extended with enzymes for conversion of glutarate to d -2HG. These enzymes may be sourced from lysine degrading bacteria as d -2HG occurs as intermediate in some of these pathways, e.g., in E. coli (Zhao and Winkler, 1996 ) and different Pseudomonaceace (Zhang et al, 2017 ; Guo et al, 2018 ; Thompson et al, 2019 ). Future work will reveal if this approach is suitable for fermentative production of d -2HG.…”
Section: Discussionmentioning
confidence: 99%
“…Further, genetically encoded fluorescent probes based on DhdR might also be developed to detect D-2-HG in vivo . Beyond reducing 2-KG to D-2-HG, in many organisms, SerA can also reduce oxalacetate to D-malate 13 . Given the importance of L-serine in metabolism, D2HGDH in these organisms has evolved to be a versatile enzyme capable of dehydrogenating both D-malate and D-2-HG to eliminate these two metabolites 40 .…”
Section: Discussionmentioning
confidence: 99%
“…D-2-HG dehydrogenase (D2HGDH) catalyzes the conversion of D-2-HG to 2-ketoglutarate (2-KG) and is the key enzyme involved in D-2-HG catabolism 7 . D-2-HG is harmful to cells and is present at rather low levels under physiological conditions, suggesting that organisms may have evolved specific mechanisms to recognize D-2-HG accumulation and enhance D2HGDH expression to catabolize D-2-HG 1013 . However, the regulation of D2HGDH expression is not fully understood and how organisms respond to the presence of D-2-HG has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%